2021
DOI: 10.3389/fonc.2021.704220
|View full text |Cite
|
Sign up to set email alerts
|

Induction Strategy for Locally Advanced Thymoma

Abstract: Surgery remains cornerstone for the management of thymoma. Complete surgical resection (R0), is recognized as the constant and significant factor for prognosis. However, in locally advanced (Masaoka-Koga stages III-IVa) thymomas, achieving R0 resection remains challenging due to local-regional invasion of the disease. Induction treatment, with the aim of reducing bulky tumor mass, offers new strategy to facilitate totally surgical resection. Herein, we reviewed recent progress and provided a comprehensive over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…This allows for downstaging of the tumor and may improve the likelihood that the tumor can be resected with negative microscopic margins. However, previous studies have demonstrated that when feasible, initial surgery provides better progression-free and overall survival [ 4 ], and chemotherapy regimens and response rates are highly variable [ 3 , 5 ]. Thus, when amenable, surgery is still recommended as first line, even in cases as ours that may require more invasive techniques [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…This allows for downstaging of the tumor and may improve the likelihood that the tumor can be resected with negative microscopic margins. However, previous studies have demonstrated that when feasible, initial surgery provides better progression-free and overall survival [ 4 ], and chemotherapy regimens and response rates are highly variable [ 3 , 5 ]. Thus, when amenable, surgery is still recommended as first line, even in cases as ours that may require more invasive techniques [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy alone is the only recommended treatment for metastatic thymomas that are not surgically resectable and not amenable to radiotherapy (stage IV), but it does not benefit stage III–IV completely resected thymomas or thymic carcinomas [ 64 , 65 ]. Advanced or metastatic thymoma and thymic carcinoma can be treated with platinum-based combination chemotherapy, which can shrink the tumor and relieve tumor-related symptoms; however, whether it can prolong survival remains to be determined, but some clinical trials are underway [ 66 ].…”
Section: The Role Of a Multidisciplinary Team In Surgical Decision Ma...mentioning
confidence: 99%
“…It is still unclear whether a good pathological response to chemotherapy leads to a good thymoma prognosis like other thoracic cancers. However, substantial necrosis of the tumor was reported in about half of thymoma patients who received induction treatment [ 5 , 6 ]. No such effect of chemotherapy was observed in the resected specimen from our patient.…”
Section: Case Presentationmentioning
confidence: 99%